Clinical value of CSF tau, p‐tau181, neurogranin and neurofilaments in familial frontotemporal lobar degeneration. (December 2021) - Rojas, Julio C.; Heuer, Hilary W.; Chen, Weiping; Czerkowicz, Julie; Graham, Danielle; Forsberg, Leah K.; Brushaber, Danielle; Appleby, Brian; Ramos, Eliana Marisa; Coppolla, Giovanni; Bordelon, Yvette M.; Botha, Hugo; et al.
Abstract: Background: Blood neurofilament light chain (NfL) is a robust predictor of phenoconversion in familial frontotemporal lobar degeneration (fFTLD). The comparative value of CSF NfL and other CSF markers of degeneration in fFTLD remains unexplored. Method: FLTD‐causing mutation carriers were recruited through ALLFTD (n = 113, 56.6% female, mean age 48.1 ± 13 years; 29 C9orf72, 16 GRN, 34 MAPT, 34 mutation non‐carriers) and prospectively evaluated for 3 years. Baseline CSF was analyzed for NfL, phosphorylated neurofilament heavy chain (p‐NfH), tau, phosphorylated tau181 (p‐tau) and neurogranin using fit‐for‐purpose immunoassays. Mixed effect linear models, with random slopes, corrected for age, sex, genotype and total intracranial volume related CSF biomarkers to longitudinal clinical variables. Result: NfL (β = 0.64, p < 0.001), p‐NfH (β = 0.68, p < 0.001) and tau (β = 0.46, p < 0.001) correlated with age. There were no differences in biomarker concentrations by phenotype or severity, except for higher NfL and p‐NfH in full phenotype, compared to prodromal disease and asymptomatic carriers. Low neurogranin (β = ‐0.39, p < 0.001), low p‐tau (β = ‐0.33, p < 0.001) and high NfL (β = 0.42, p < 0.001) correlated with worse baseline disease severity measured by the CDR ® Dementia Staging Instrument plus behavior and language domains from the National Alzheimer's Disease Coordinating Center FTLD module sum of boxes (CDR ® +NACC‐FTLDsb), and with other measures of global cognition, instrumental and daily function, and frontal and temporal brain volumes. Regardless of genotype, the predicted annualized rate of CDR ® +NACC‐FTLDsb score worsenings per higher baseline CSF biomarker Log pg/mL were tau: 3.0 ± 0.2, NfL: 2.8 ± 0.2 and p‐NfH: 2.8 ± 0.2. High tau, NfL and p‐NfH also predicted worsening in other measures of global cognition and instrumental and daily function. Neurogranin and p‐tau did not predict clinical decline. Conclusion: CSF tau, p‐tau, neurogranin, NfL and p‐NfH reflect important aspects of disease severity in fFTLD. In contrast to Alzheimer's disease, low p‐tau and neurogranin are inversely related to clinical severity, which suggests a distinctive pathophysiological process and has implications for therapeutic development. CSF NfL, p‐NfH and tau have strong prognostic value in fFTLD.